2018
DOI: 10.1186/s13005-017-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Head circumference - a useful single parameter for skull volume development in cranial growth analysis?

Abstract: BackgroundThe measurement of maximal head circumference is a standard procedure in the examination of childrens’ cranial growth and brain development. The objective of the study was to evaluate the validity of maximal head circumference to cranial volume in the first year of life using a new method which includes ear-to-ear over the head distance and maximal cranial length measurement.Methods3D surface scans for cranial volume assessment were conducted in this method comparison study of 44 healthy Caucasian ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The LDSC intercept of 1.02 is close to 1, suggesting that the observed inflation (λ GC = 1.118) in genetic signal is mostly due to polygenicity rather than population stratification 22 (see Supplementary Note 1). The UKB GWAS results were then meta-analyzed with GWAS results from two previously published studies: one on ICV from the ENIGMA consortium 13 (N = 11,373), the other on HC, a proven proxy of BV [23][24][25] (also see Supplementary Note 2), from a recent GWAS meta-analysis 11 of adults and children (N = 18,881). This led to a total sample size of 47,316 unrelated Europeans ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The LDSC intercept of 1.02 is close to 1, suggesting that the observed inflation (λ GC = 1.118) in genetic signal is mostly due to polygenicity rather than population stratification 22 (see Supplementary Note 1). The UKB GWAS results were then meta-analyzed with GWAS results from two previously published studies: one on ICV from the ENIGMA consortium 13 (N = 11,373), the other on HC, a proven proxy of BV [23][24][25] (also see Supplementary Note 2), from a recent GWAS meta-analysis 11 of adults and children (N = 18,881). This led to a total sample size of 47,316 unrelated Europeans ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…a genetic correlation coefficient near one), we considered HC and ICV to be related proxy measures of an underlying phenotype, which we termed final cranial dimension. This also suggests that estimated skeletal volume, a combination of HC, cranial height and cranial length 52 , might represent a more accurate, easily accessible and inexpensive measure to enhance power for future genetic analysis using a multi-trait approach 53 in combination with ICV, exploiting similar volumetric properties.…”
Section: Discussionmentioning
confidence: 99%
“…The LDSC intercept of 1.02, however, suggested that the observed inflation in 5 genetic signal is mostly due to polygenicity and unlikely to be driven by population stratification 196 (see Supplementary Results). The UKB GWAS results were then meta-analyzed with GWAS results from two previously published studies 295,296 : one on intracranial volume (ICV) from the ENIGMA consortium 297 (N=11,373), the other on head circumference (HC), a proven proxy of BV [298][299][300] (also see Supplementary Methods), from a recent GWAS meta-analysis 301 of adults and children (N=18,881). This led to a total sample size of 47,316 unrelated Europeans (Supplementary Fig.…”
Section: Gwas Meta-analysis Of Brain Volumementioning
confidence: 99%